2013
DOI: 10.1152/ajpgi.00448.2012
|View full text |Cite
|
Sign up to set email alerts
|

Role of prostaglandin D2 in mast cell activation-induced sensitization of esophageal vagal afferents

Abstract: S. Role of prostaglandin D 2 in mast cell activationinduced sensitization of esophageal vagal afferents. Am J Physiol Gastrointest Liver Physiol 304: G908 -G916, 2013. First published March 7, 2013 doi:10.1152/ajpgi.00448.2012.-Sensitization of esophageal afferents plays an important role in esophageal nociception, but the mechanism is less clear. Our previous studies demonstrated that mast cell (MC) activation releases the preformed mediators histamine and tryptase, which play important roles in sensitizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…who showed that DP 1 and DP 2 receptors are present in guinea pig oesophageal nodose ganglia by immunostaining and Western blot with similar antibody, and by RT‐PCR 29. Presently, in male guinea pig trigone and proximal urethra, we found both DP 1 and DP 2 receptors located in the urothelium and smooth muscle and that DP 1 receptors were prominent on the membranes of smooth muscle cells, in agreement with our previous study on bladder detrusor 18.…”
Section: Discussionsupporting
confidence: 92%
“…who showed that DP 1 and DP 2 receptors are present in guinea pig oesophageal nodose ganglia by immunostaining and Western blot with similar antibody, and by RT‐PCR 29. Presently, in male guinea pig trigone and proximal urethra, we found both DP 1 and DP 2 receptors located in the urothelium and smooth muscle and that DP 1 receptors were prominent on the membranes of smooth muscle cells, in agreement with our previous study on bladder detrusor 18.…”
Section: Discussionsupporting
confidence: 92%
“…For example, cholecystokinin and serotonin act via vagal afferent fibers to transmit gastrointestinal information to the brain [23]. Vagus afferent nerves are also known to be activated in response to various substances, such as interleukin 1β [24], prostaglandin D 2 , and reactive oxygen species [25, 26]. Interestingly, Gidron et al [27] suggested that the vagus nerve can transmit information about cancer progression to the brain through peripheral proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Agonizing DP1 in mast cells using BW 245C caused these immune cells to induce an increase in neuronal excitability. 77,78 This observation is of particular interest given that it has recently been shown that conditioned media from SOD1G93A glia can induce motor neuron hyperexcitability in rat spinal cord slices. 27 Further studies of whether activated microglia share some properties with mast cells may be warranted.…”
Section: Microgliamentioning
confidence: 94%
“…76 Additional experiments have also implicated DP1 in mast cell induced neuronal hyperexcitability. 77,78 In these studies DP1 inhibition by BW A868C reduced the levels of extraneous firing when mast cells were co-cultured with primary neurons. Agonizing DP1 in mast cells using BW 245C caused these immune cells to induce an increase in neuronal excitability.…”
Section: Microgliamentioning
confidence: 97%